Phosphoramidates: Molecular Packing and Hydrogen Bond Strength in Compounds Having a P(O)(N)n(O)3-n (n = 1, 2, 3) Skeleton - Pourayoubi, Mehrdad; Sabbaghi, Fahimeh; Divjakovic, Vladimir; Tarahhomi, Atekeh (IntechOpen, 2012)
None